Value of Injection from Residential PV with Storage for the Bulk Power System. - Martín-Rivas, Sebastián; Pérez-Ruiz, Juan; López-Pérez, Pablo (IEEE, 2019)
This paper presents a model to assess the value of power injection from residential installations, with photovoltaic (PV) generation and/or electric storage, to the main grid. This model is posed as a multi-period two-stage stochastic economic dispatch, including ramping constraints and operating reserves, from the point of view of a central operator. Two sources of uncertainty are distinguished and represented as mid- and short-term scenarios: mid-term variability along the year and short-term forecasting errors. A case study, based on the Spanish power system, is presented to show the value of injection on both the operation costs and CO2 emissions. Results obtained allow us to provide some recommendations on the deployment of these residential installations.
https://conferences.ieeeauthorcenter.ieee.org/author-ethics/guidelines-and-policies/post-publication-policies/
Keywords: Edificios - Equipamiento eléctrico; Instalaciones fotovoltaicas; Power injection; Residential fotovoltaic generation; Residential battery storage; Stochastic Economic Dispatch; System operation cost (OPEX); CO2 emissions